2000
DOI: 10.1088/0264-9381/17/19/302
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence principle, higher-dimensional Möbius group and the hidden antisymmetric tensor of quantum mechanics

Abstract: We show that the recently formulated Equivalence Principle (EP) implies a basic cocycle condition both in Euclidean and Minkowski spaces, which holds in any dimension. This condition, that in one-dimension is sufficient to fix the Schwarzian equation [6], implies a fundamental higher dimensional Möbius invariance which in turn univocally fixes the quantum version of the Hamilton-Jacobi equation. This holds also in the relativistic case, so that we obtain both the time-dependent Schrödinger equation and the Kle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
135
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(138 citation statements)
references
References 42 publications
3
135
0
Order By: Relevance
“…In this paper we offer a solution to this puzzle. We demonstrate the absence of trajectories in the derivation of the QHJE from point transformations leading to the trivial hamiltonian [11][12][13][14][15][16][17][18]. The basic point is that trajectories can only be defined by time parameterisation of them, and include the Bohm-de Broglie pilot wave representation and Floyd's time parameterisation [19][20][21][22][23][24][25][26][27] by using Jacobi theorem.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this paper we offer a solution to this puzzle. We demonstrate the absence of trajectories in the derivation of the QHJE from point transformations leading to the trivial hamiltonian [11][12][13][14][15][16][17][18]. The basic point is that trajectories can only be defined by time parameterisation of them, and include the Bohm-de Broglie pilot wave representation and Floyd's time parameterisation [19][20][21][22][23][24][25][26][27] by using Jacobi theorem.…”
Section: Introductionmentioning
confidence: 93%
“…Such a transformation leads to a basic cocycle condition which, in turn, implies that the analog of the Hamilton characteristic function must satisfy the quantum analog of the stationary HJ equation. The derivation extends to the higher dimensional non-stationary case and to the relativistic case as well [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These facts imply that the concept of a quantum is not absolute, but relative to the quantum theory used to measure it [1]. In particular classical and quantum, for long known to be intimately related [10], are not necessarily always the same for all observers on phase space. In this letter we have analysed the dependence of the notion of a quantum on the complex-differentiable structure chosen on classical phase space.…”
Section: Discussionmentioning
confidence: 99%
“…Deriving quantum mechanics from an equivalence postulate, Faraggi and Matone showed that the Schrödinger wave function must have the form [1,2,3,4] φ(x) = ∂S 0 ∂x…”
Section: Introductionmentioning
confidence: 99%